Innovative Strategies and Applications in Case Study Methodology- A Review - Varsha Rokade (AG Volumes, 2024)
This review paper delves into the multifaceted landscape of case study methodology, including its various types, strategic application, research methodologies, innovative strategies, and various applications across disciplines. It defines the various types of case studies, clarifies their unique research objectives and purposes. The utility of case study research in providing rich, framed insights into complicated issues is underscored through an examination of its strategic methodology. Methodological approaches for data acquisition and analysis are outlined, as well as considerations for reliability and validity. There is a discussion of innovative strategies, including participatory design, longitudinal studies, and mixed-methods approaches, to enhance case study research. Furthermore, the paper emphasises the extensive applications of case study methodology in various fields. This paper provides a comprehensive overview that clarifies the importance and adaptability of case study methodology in modern research endeavours.